Zaščitna vloga astrocitov pri zastrupitvi z ogljikovim monoksidom in optimizacija zdravljenja - Krajnc, Ivana (Zdravniški vestnik, 2022)
Background: Carbon monoxide (CO) poisoning impairs astrocyte and neuron performance. Treatment with hyperbaric oxygen (HBO) can prevent late neuropsychological impairment. We investigated the effect of CO and HBO on the early pro - cesses of cell death in neuronal and mixed culture and determined whether the level of glutathione in astrocytes changes after exposure to CO and HBO and whether it could represent a potential new target for the treatment of CO poisoning. Methods: Primary astrocytes, neuronal and mixed cultures of the rat cerebral cortex were exposed to CO in the air and then to 24-hour normoxia, during which the cells were exposed to 100 % oxygen at 3 bar pressure for 1 hour at various time intervals. We measured the activity of lactate dehydrogenase (LDH) and caspase 3/7 in neuronal and mixed cell cultures and levels of glutathione in astrocytes. Results: CO induced an increase in LDH and caspase 3/7 activity in neuronal culture, but only in caspase 3/7 activity in mixed cultures. After treatment with HBO, there was an increase in LDH activity in neuronal and in caspase 3/7 activity in mixed culture. CO caused a decrease in total glutathione (GSHt), an increase in glutathione disulfide (GSSG), and a de - crease in GSH/GSSG in astrocytes, and after CO/HBO, there was an increase in GSHt, a decrease in GSSG and an increase in GSH/GSSG. Conclusions: Differences in the cytotoxic effect of CO and the protective role of HBO in neuronal, mixed and astrocyte cul- ture show that neurons growing in the absence of astrocytes are more susceptible to the harmful effects of CO compared to mixed culture and suggest that astrocytes attempt to protect neurons that depend on them for glutathione synthesis during oxidative stress.
Keywords: glutathione; glutation; hiperbarična oksigenacija; hyperbaric oxygenation; neurons; nevroni